Analisis Penetapan Biaya Produksi Dan Penentuan Harga Jual Iklan Pada PT Radio Suara Tiara Indah - Supriyati Supriyati; Octa Reni Setiawati; Vira Sandayanti (Holistik Jurnal Kesehatan, 2019)
SELF-EFFICACY IN A PROFESSIONAL COMPETENCY TEST AMONG MEDICAL STUDENTSBackground: To have competence as a doctor, the medical student have to pass examination a Professional Competency Test to obtain doctoral diplomas from educational institutions and competency certificates from institutions that authorized. The data obtained based on passing student examination a Professional Competency Test at Malahayati University showed an average number of 48.75%. Many factors can influence the success of student learning in students, one of which is the efficacy of self efficacy. Individuals who have high self efficacy will direct someone to better achievement in various fields.Purpose: This study aims to examine the relationship between self efficacy with passing number student examination a Professional Competency Test at Malahayati University.Methods: The variable in this study is self-efficacy as an independent variable and passing number student examination a Professional Competency Test as a dependent variable. The research sample in this study were medical profession students who passed examination a Professional Competency Tes. The method of collecting data was using the scale self efficacy and a Professional Competency Tes document. Data analysis method uses product moment.Results: The value are r 0.673 with p = 0,000 where (p <0.01) means that there is a very significant positive relationship between self efficacy and passed student examination a Professional Competency Test at Malahayati University, Bandar Lampung.Keywords: Self Efficacy, student, examination, Professional Competency TestPendahuluan: Mahasiswa dikatakan memiliki kompetensi sebagai seorang dokter jika telah menuntaskan Uji Kompetensi Mahasiswa Program Profesi Dokter (UKMPPD) untuk memperoleh ijazah dokter dari institusi pendidikan dan sertifikat kompetensi dari institusi yang berwenang. Data yang diperoleh berdasarkan tingkat ketidaklulusan UKMPPD mahasiswa program profesi dokter Universitas Malahayati menunjukkan angka rata-rata sebesar 48,75%. Banyak faktor yang dapat mempengaruhi keberhasilan belajar mahasiswa pada mahasiswa, salah satunya adalah self efficacy.Self efficacy. Individu yang memiliki self efficacy yang tinggi akan mengarahkan seseorang pada prestasi yang lebih baik dalam berbagai bidang.Tujuan: Penelitian ini bertujuan untuk meneliti hubungan antara self efficacy (keyakinan akan kemampuan diri) dengan kelulusan retaker UKMPPD di Universitas Malahayati.Metode: Variabel dalam penelitian ini adalah self efficacy sebagai variabel bebas dan kelulusan retaker UKMPPD. Sampel penelitian dalam penelitian ini adalah mahasiswa profesi dokter yang menjadi retaker pertama pada ujian UKMPPD.Metode Pengumpulan data dengan menggunakan skala self efficacy dan dokumen kelulusan UKMPPD. Metode analisis data menggunakan product moment. Hasil: Nilai r sebesar 0,673 dengan P = 0,000 dimana ( p < 0,01 ) artinya ada hubungan positif yang sangat signifikan antara self efficacy dengan kelulusan retaker UKMPPD Universitas Malahayati Bandar Lampung.